An Act for Forming and Regulating the Militia of the Province of Pennsylvania, 627, PA. CONS. STAT. (WM Stanley Ray 1898) (Law Passed 1757). - (:unkn) unknown (My University, 1757)
That all arms, military accoutrements, gunpowder and ammunition of what kind soever, any papist or reputed papist within this province hath or shall have in his house or houses or elsewhere one month after the publication of this act, shall be taken from such papist or reputed papist by warrant under the hands and seals of any two justices of the peace, who are hereby empowered and required to issue a warrant for search as often as they shall receive information or have good cause to suspect the concealment of arms and ammunition in the houses of any papist or reputed papist; and the said arms, military accoutrements, gunpowder and ammunition so taken shall be delivered to the colonel of the regiment within whose district the said arms are found, by him to be safely kept for the public use. And if any such papist or reputed papist, shall have any arms, military accoutrements, gunpowder or ammunition after the time so as aforesaid limited, the same being so seized shall be forfeited: And if any such papist or reputed papist shall attempt to conceal such arms, military accoutrements, gunpowder and ammunition as aforesaid, or refuse to declare and manifest the same to the said justices of the peace or to any other person authorized by warrant to search for, seize and take the same, every such person so offending shall be imprisoned by warrant from the said justices for the space of three months, without bail or mainprize."
Keywords: POSSESSION - DANGEROUS PERSONS